Optimal design and verification of lateral stiffness of suspension system for suspended monorail train - HUANG Xiaocui; JIA Xiaoping; FU Maohai; YANG Liangliang (机车电传动)
Against the problem of insufficient lateral flexibility due to the design space limitation of secondary springs of the bogie for a suspended monorail train, an equivalent restoring stiffness formula was deduced from the linear theory of small swing angles for the four-linkage suspension mechanism. Based on the formula, the geometric parameters optimization of suspension system was completed, and the lateral stiffness of the suspension system was improved to the level equivalent to the secondary air spring used on metro trains. Combined with the actual design cases of suspended monorail trains, the four-link suspension mechanism was analyzed from the view of kinematics and dynamics using the multi-rigid-body dynamics approach. The applicability scope and limitation of the equivalent restoring stiffness formula were summarized, and a 3D coupling dynamics model for the whole train was established to analyze and verify the effectiveness of the optimized design solution of the suspension system. The results show that the design solution by reasonably matching the geometric parameters of the four-linkage mechanism can significantly improve the lateral riding quality of the train, but when the train passes through a small radius curve, it will cause more dynamic deviation of the train body.